Urinary Tract Tumors, Biology and Risk for Artificial Sweeteners Use with Particular Emphasis on some South American Countries - Andreatta, M. M.; Navarro, A.; Eynard, A. R. (Current Nutrition & Food Science, 2008)
Bladder tumors predominantly occur in high-income countries. However, South America deserves particular attention since is it is made up of countries with striking differences in their GNP per capita, representing a “chessboard” field for the study of tumor risk related to the environment. In recent times, a so-called “healthy” culture has emerged with people beginning to be conscious of the effects of food and nutrition on well-being and the risk of disease linked to being overweight. As a result of the so-called “healthy” culture, many people have substituted sugar for different types of Artificial Sweeteners (AS) which also have lower costs of production and commercialization. This article reviews and critically discusses the current literature regarding the correlations between AS and Urinary Tract Tumors worldwide, particularly taking into account recent data of case-control studies in South America, an area having distinctive dietary habits and food culture.
Keywords: South America